2021
DOI: 10.22266/ijies2021.0430.25
|View full text |Cite
|
Sign up to set email alerts
|

IoT Based Real-Time Monitoring of Phytoremediation of Wastewater using the Mathematical Model Implemented on the Embedded Systems

Abstract: This paper presents the Internet of things (IoT) technology for real-time monitoring of wastewater phytoremediation. Phytoremediation is a technique to remove pollutants from the wastewater using the plants. A conventional method to monitor the phytoremediation performance is by taking the samples of the contaminants from a site and measuring them at the laboratory. This method needs many works for data preparation and analysis. A recent development on the IoT technology may eliminate such tasks by a real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Recently, industrial embedded systems [ 14 ] have drawn significant attention when applied to industrial process control [ 15 ] and monitoring [ 16 , 17 , 18 ] and edge intelligent systems [ 19 , 20 ]. Unlike the loose requirements found in traditional Industrial IoT (IIoT) applications, resource-constrained industrial embedded systems set stricter requirements for low latency and small memory.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, industrial embedded systems [ 14 ] have drawn significant attention when applied to industrial process control [ 15 ] and monitoring [ 16 , 17 , 18 ] and edge intelligent systems [ 19 , 20 ]. Unlike the loose requirements found in traditional Industrial IoT (IIoT) applications, resource-constrained industrial embedded systems set stricter requirements for low latency and small memory.…”
Section: Introductionmentioning
confidence: 99%
“…For automation-based activities, a micro-sized computer was found that functions to control other devices called microcontrollers [1][2] [3]. Arduino MKR is an example of a microcontroller created for makers and engineers to quickly prototype IoT projects [4] [5][6] [7]. The Arduino MKR board has an RTC IC embedded.…”
Section: Introductionmentioning
confidence: 99%